حركة الإنفاق الاستثماري في ظل قانون الاستثمار رقم 10 لعام 1991 وتعديلاته وتقييم نتائج تطبيقه منذ صدوره حتى منتصف عام 2001 - هرمز نور الدين; خلـف محمد; اسـماعيل محمد محرز (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تظهر دراسة حركة الإنفاق الاستثماري في ظل قانون الاستثمار رقم 10 لعام 1991 وتعديلاته، التطور الحاصل في البنية الهيكلية للمشاريع المشملة بأحكامه وزيادة أعدادها، واستحواذ قطاع الصناعة على معظم استثماراته من حيث التكلفة وتأخرها عن قطاع النقل من حيث العدد، وتدني الاستثمارات في قطاع الزراعة من حيث العدد والتكلفة عما هي في قطاعي الصناعة والنقل، إضافة إلى استقطاب المشاريع الفردية وشركات الأشخاص لمعظم المشاريع، وتركزها في محافظة دمشق وريف دمشق وحلب. وبعد تقييم نتائج تطبيقه حتى نهاية عام 2000، يلاحظ ارتفاع نسبة تنفيذ المشاريع الصناعية والزراعية المشملة بأحكامه في السنوات الأولى من صدوره وتراجعها في باقي السنوات، وارتفاع عدد المركبات بشكل زاد عن حاجة السوق الفعلية إليها، وقلة عدد فرص العمل المتاحة قياساً لما يدخل إلى سوق العمل السورية سنوياً من طالبي العمل. The studying of the investment spending activity under the provisions of investment law No. 10 year 1991 and its modifications will reveal the development in structure of the said projects besides increasing numbers of these projects, where the industry sector occupies most of its investment activities regarding the costs and comes next to the transport sector regarding number of projects in addition to reduced number of agricultural projects regarding number and costs compared to sectors of industry and transport, besides that the individual projects and private corporations attract most of the projects which are mainly centered in Damascus, Aleppo and Damascus Countryside region. Following to appraisal of the results produced by application of this law till end of year 2000 we notice a rising ratio of executing agricultural and industrial projects covered by this law’s provisions during the few years followed its issuing then this ratio is declined during the years which followed, we notice besides, and increase in number of vehicles to become surplus to the actual need with a decrease of work apportunities available comparing with the annual number of those seek employment in Syria.